1985
DOI: 10.1099/0022-1317-66-4-871
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Antibodies, Macrophages and Virulence in Mouse Cytomegalovirus Infection

Abstract: SUMMARYThe infectivity of tissue culture-passed mouse cytomegalovirus (MCMV) for resident mouse peritoneal macrophages in the presence of serial dilutions of antiviral antibody was studied by fluorescent antibody staining and virus yields. Although MCMV was neutralized by high concentrations of antiserum, there was a twofold enhancement of infectivity by subneutralizing antibody concentrations. On further dilution of antiserum, significant neutralization appeared again. When F(ab')_, fragments of anti-MCMV IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 16 publications
(15 reference statements)
1
21
0
Order By: Relevance
“…Virulence of cell-grown virus was increased on passage from >2.8 x 105 p.f.u./LD50 to 450 p.f.u./LDso after one passage and 310 p.f.u./LD50 after two passages but was still considerably less virulent (10-fold) than SGV (Table 2). It seems likely that a cell-adapted variant has been selected since the cellgrown virus has now been passaged up to 20 times in MEF cultures (Inada et al, 1985). This contrasts with the original studies where cell-grown viruses had been passaged a maximum of five times and is supported by the observation that non-ts PP330/1, passaged up to seven times in tissue culture as the ts mutants were, was fully virulent after one mouse passage (Table 2).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Virulence of cell-grown virus was increased on passage from >2.8 x 105 p.f.u./LD50 to 450 p.f.u./LDso after one passage and 310 p.f.u./LD50 after two passages but was still considerably less virulent (10-fold) than SGV (Table 2). It seems likely that a cell-adapted variant has been selected since the cellgrown virus has now been passaged up to 20 times in MEF cultures (Inada et al, 1985). This contrasts with the original studies where cell-grown viruses had been passaged a maximum of five times and is supported by the observation that non-ts PP330/1, passaged up to seven times in tissue culture as the ts mutants were, was fully virulent after one mouse passage (Table 2).…”
Section: Discussionmentioning
confidence: 93%
“…This may also explain the reduced virulence of the acyclovir-resistant mutants and the avirulence of ts6 (Table 2) which were derived from cell-grown virus (Sandford et al, 1985 ;Sandford & Burns, 1988). Finally, although the presence of antibody does enhance the virulence of cell-grown virus passaged 10 to 20 times, it does not fully restore virulence to that of SGV (Inada et al, 1985;Inada & Mims, 1985). Together these observations clearly suggest that factors in addition to virion-bound non-neutralizing antibody acquired in vivo are involved in MCMV virulence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains of MCMV, virus assay method, strain of mice, macrophage culture method, preparation of anti-MCMV serum and fluorescent antibody (FA) methods are described in the accompanying paper (Inada et al, 1985).…”
mentioning
confidence: 99%
“…In other families, studies have been limited to relatively few viruses, but ADE has been reported with the following: rabbit pox virus [1], family Poxviridae; rabies virus and fish rhabdoviruses, family Rhabdoviridae [15]; Reovirus type 3, family Reoviridae; murine cytomegalovirus, family Herpesviridae [16]; and feline infectious pancreatitis virus, family Coronaviridae [17]. Failure to detect ADE has been reported with only two viruses, Mengo virus, family Picornaviridae, and herpes simplex virus, family Herpesviridae [4].…”
Section: Viruses Producing Adementioning
confidence: 99%